Rancangan dan Pembuatan Front end Website Kelurahan Tanjunganom - Anggraeni Lestari, Fika; Resad Setyadi (Infoman's : Jurnal Ilmu-ilmu Informatika dan Manajemen, 2024)
Currently, the pace of development of information technology is very rapid. Information technology is very necessary in human life. One of the functions of information systems technology is to help or encourage human work to be more efficient and productive. Information systems development includes various methods and platforms. Platforms that can be used in developing information systems are mobile, web or desktop platforms. This research aims to identify a web-based information system development model. The method used in this research is the Extreme Programming method. The Extreme Programming software development method aims to improve software quality and meet the ever-changing needs of users. In this era of rapid development of information technology, the existence of information system technology has become very crucial in human life. Information system development includes various methods and platforms, such as mobile, web or desktop platforms. This research has a specific aim, namely identifying a web-based information system development model. In this context, the method chosen to use is the Extreme Programming (XP) method. XP's approach to software development is designed to improve software quality and respond to the dynamics of changing user needs.